Comparison of outer membrane porin proteins produced by Escherichia coli and Salmonella typhimurium. - Lee, D R (1980)
The OmpC, OmpF, and Lc (NmpC) porin proteins of Escherichia coli K-12 have been shown to be similar to the OmpC (36K), OmpF (35K) and OmpD (34K) porin proteins of Salmnella typhimurium LT2 in terms of function, regulation of expression, and, in the case of OmpC and OmpF proteins, equivalence of the genetic loci determining their production. However, the corresponding pairs of proteins from these two species showed only limited similarity in peptide maps and no similarity in terms of migration on polyacrylamide gels.